A mathematical model for Creutzfeldt Jacob Disease (CJD). (November 2018) - Salman, S.M.; Ahmed, E.
Highlights: A mathematical model for Creutzfeldt Jakob Disease (CJD) is given. Local dynamics of the model are addressed. Co-dimension one bifurcation is analyzed. The disease will persist in the population if increasing the growth rate of the healthy prions. Abstract: Creutzfeldt Jakob Disease (CJD) is a fatal disease which is transmitted by the ingestion of infectious materials (mainly BSE-contaminated beef). Here a simple mathematical model of its progress is given. Local stability analysis of fixed points of the model is studied. Moreover, codimension-one bifurcation analysis of fixed points is discussed. The model has a variety of bifurcation types such as transcritical, pitchfork and flip bifurcations. Numerical simulations are performed to illustrate analytical results obtained. Despite being a simple model, it discusses a non expected behavior which is increasing the parameter a, the growth rate of the healthy prions, the disease will persist in the population.